2020
DOI: 10.11005/jbm.2020.27.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Rosae Multiflorae Fructus Extracts on the Receptor Activator of NF-κB Ligand-Induced Osteoclastogenesis through Modulation of P38- and Ca2+-Mediated Nuclear Factor of Activated T-Cells Cytoplasmic 1 Expression

Abstract: Background: Rosae Multiflorae fructus (RMF), known to have anti-inflammatory and antioxidant properties, has been used as a traditional remedy for inflammatory diseases such as arthritis in Eastern Asia. However, its effect on osteoclasts, which play a crucial role in resorptive inflammatory bone diseases, is yet to be elucidated. Methods: The effect of extract of RMF (RMF-E) on receptor activator of nuclear factor-κB ligand (RANKL)mediated osteoclastogenesis was examined by tartrate-resistant acid phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Differences in the cell culture model, tested flavonoids, levels, and exposure time, evaluated parameters, and, importantly, the nature of the functionalized biomaterial, hinder the establishment of patterns. Nevertheless, reported information strongly supports the positive role of flavonoids in bone formation [ 68 ]. However, in the present work, with the used experimental protocol, the relative contribution of the particles physicochemical profile or the presence of the RH extract is not known.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Differences in the cell culture model, tested flavonoids, levels, and exposure time, evaluated parameters, and, importantly, the nature of the functionalized biomaterial, hinder the establishment of patterns. Nevertheless, reported information strongly supports the positive role of flavonoids in bone formation [ 68 ]. However, in the present work, with the used experimental protocol, the relative contribution of the particles physicochemical profile or the presence of the RH extract is not known.…”
Section: Discussionmentioning
confidence: 71%
“…RH contains high levels of flavonoids, a major subclass of polyphenols that have been shown to promote osteoblast differentiation, which ultimately results in bone formation [ 67 ]. Some of these compounds appear to inhibit osteoclastogenesis [ 68 ]. Still, there are also studies reporting different effects in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…Rosa multiflora is divided into RMF and Rosa multiflora Thunb (RM). Several recent studies have shown that RM effectively improves sleep quality and acts as an antioxidant and anti-inflammatory agent [ 17 , 18 ]. In addition, RMF exhibits anti-atopic, anti-allergic, and anti-inflammatory effects similar to those of Donguibogam in Korean Oriental medicine [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported that natural products, such as herbs, botanical extracts, and dietary supplements, have been studied for their potential effects on obesity-related factors [ 13 ]. In this study, we attempted to analyze Rosae multiflorae fructus (RMF), a representative natural product for treating circulatory diseases, as specified in Donguibogam, an important book of Korean medicine [ 14 ]. However, the role of RMF in liver disease remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoclast differentiation culture was performed with mouse BMMs as previously described. [ 15 , 16 ] In brief, bone marrow cells were flushed from the tibiae and femurs of 5-week-old female ICR mice and cultured in α-minimal essential medium (α-MEM) containing 10% fetal bovine serum (FBS) overnight on culture dishes. Adherent cells were discarded, and nonadherent cells were further incubated with 30 ng/mL M-CSF in Petri dishes for 3 days.…”
Section: Methodsmentioning
confidence: 99%